2014
DOI: 10.1920/wp.ifs.2014.1406
|View full text |Cite
|
Sign up to set email alerts
|

Can survey participation alter household saving behavior?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Although Crossley et al . () estimated the effect of participation in a survey module that was fielded only once, their results lend support to the hypothesis that (repeated) survey participation can alter respondents’ behaviour. Moreover, their identification strategy, which uses an IV approach, can be applied to the estimation of panel conditioning effects, and that is the approach which we take in this study.…”
Section: Introductionmentioning
confidence: 65%
“…Although Crossley et al . () estimated the effect of participation in a survey module that was fielded only once, their results lend support to the hypothesis that (repeated) survey participation can alter respondents’ behaviour. Moreover, their identification strategy, which uses an IV approach, can be applied to the estimation of panel conditioning effects, and that is the approach which we take in this study.…”
Section: Introductionmentioning
confidence: 65%
“…The possibility of awareness effects with respect to inconspicuous survey questions has been documented in Crossley et al . (). Comparable effects may occur in the labour market.…”
Section: Resultsmentioning
confidence: 97%
“…Further, Crépon et al (2014) reported that the mere notification of a planned training assignment has effects on the unemployment exit probability. In a related endeavour, Crossley et al (2014) documented that mere exposure to specific questions in a survey can alter subsequent behaviour. Exploiting randomized assignment to survey modules within the 'Longitudinal Internet studies for the social sciences' panel survey, they found that households answering questions on expenditures and needs in retirement significantly changed their non-housing saving rates.…”
Section: Introductionmentioning
confidence: 99%
“…Every measurement we take from human beings has the potential to affect the human behavior we hope to measure (Fitzsimons and Moore, 2008; Warren and Halpern-Manners, 2012; Zwane et al, 2011). Even as scientific attention to these issues grows (Crossley, de Bresser, Delaney, and Winter, 2014; Schneider, Tahk and Krosnick, 2007; Williams, Block, and Fitzsimons, 2006; Wilson and Howell, 2006), the demands for more repetitive measurement— especially multiple measures of the same person—are growing at an even faster pace (Dunton and Atienza, 2009; Ginexi et al, 2013; Schlam et al, 2012). We focus on repeated measures over time—an area of substantial investment of effort, with recent breakthroughs significantly enhancing our ability to conduct measurements of the same people frequently.…”
Section: 1 Introductionmentioning
confidence: 99%